2016
DOI: 10.1089/jmf.2015.3527
|View full text |Cite
|
Sign up to set email alerts
|

Artemisia annuaLeaf Extract Attenuates Hepatic Steatosis and Inflammation in High-Fat Diet-Fed Mice

Abstract: Artemisia annua L. (AA) is a well-known source of the antimalarial drug artemisinin. AA also has an antibacterial and antioxidant activity. However, the effect of AA extract on hepatic steatosis induced by obesity is unclear. We investigated whether AA extract prevents obesity-induced insulin resistance and hepatic steatosis in high-fat diet (HFD)-fed mice. Mice were randomly divided into groups that received a normal chow diet or HFD with or without AA for 12 weeks. We found that AA extract reduced insulin re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 37 publications
4
37
0
Order By: Relevance
“…Accordingly, inhibition of PPAR‐γ and C/EBP‐α can affect the growth and differentiation of adipocytes . On the other hand, SREBP‐1 c plays an essential role in lipid synthesis and metabolism by regulating its target lipogenic genes, including FAS , VLDLR and Scd 1 . In this study, our results showed that BMH473 may inhibit the adipogenesis and reduce the lipid accumulation in 3T3‐L1 preadipocytes, by downregulating the protein expression levels of PPAR‐Ɣ, C/EBP‐α and SREBP‐1 c, as well as the mRNA expression levels of VLDL , FAS and Scd 1 (Figure ).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Accordingly, inhibition of PPAR‐γ and C/EBP‐α can affect the growth and differentiation of adipocytes . On the other hand, SREBP‐1 c plays an essential role in lipid synthesis and metabolism by regulating its target lipogenic genes, including FAS , VLDLR and Scd 1 . In this study, our results showed that BMH473 may inhibit the adipogenesis and reduce the lipid accumulation in 3T3‐L1 preadipocytes, by downregulating the protein expression levels of PPAR‐Ɣ, C/EBP‐α and SREBP‐1 c, as well as the mRNA expression levels of VLDL , FAS and Scd 1 (Figure ).…”
Section: Discussionmentioning
confidence: 51%
“…56,57 On the other hand, SREBP-1 c plays an essential role in lipid synthesis and metabolism by regulating its target lipogenic genes, including FAS, VLDLR and Scd 1. [58][59][60][61][62] In this study, our results showed that BMH473 BMH473 demonstrated a significant hypoglycaemic activity by activating phosphorylation of AMPK-ACC, and then attenuating hepatic steatosis and gluconeogenesis in obese T2DM rats. In conclusion, BMH473 has the potential to be developed as an anti-diabetic drug, and offers an obvious advantage over anti-hyperlipidaemic therapy.…”
Section: Further In Vivo Experiments Revealed That Bmh473 Significantlymentioning
confidence: 88%
“…These compounds exhibit extensive biological and medicinal applications such as anti-tumor, antidiabetic, anti-inflammatory, antioxidant, antimicrobial, and analgesic effects (125). Reviews have shown that many terpenoids compounds including betulinic acid, artemisinin, as well as ursolic acid gentiopicroside (126)(127) represented important roles to treat the NAFLD. deMelo et al (2009) demonstrated that betulinic acid by affecting the AMPK-SREBP signaling pathway (considerable decreases in hepatic AMPK phosphorylation, and improved activation of SREBP1) significantly decrease the hepatic lipid accumulation in mice (128).…”
Section: Terpenoidsmentioning
confidence: 99%
“…It is the source of artemisinin, an anti-malarial agent with a sesquiterpene trioxane lactone 21 . Because of the presence of flavonoids, essential oils, and sesquiterpene lactones, A. annua has anti-oxidant, anti-cancer, anti-microbial, anti-adipogenic, and anti-inflammatory activities 22 26 . Many studies have used artemisinin, isolated from A. annua , and its natural and semi-synthetic derivatives to develop more effective anti-malarial agents and to find new treatments for other diseases, including cancer 27 30 .…”
Section: Introductionmentioning
confidence: 99%